Functional analysis of subunit MRB3010 of the mitochondrial binding complex 1 in Trypanosoma brucei. - Ridlon, Lucie (Jihočeská univerzita, 2010)
This thesis concerns a putative protein complex called the Mitochondrial Binding Complex 1 (MRB1), subunits of which have essential functions in the RNA metabolism of both procyclic and bloodstream forms of T. brucei. The focus of this study is on one of the subunits, called MRB3010. It was shown that this subunit of MRB1 complex is essential in both stages of T. brucei and the MRB3010 silencing affects the maxicircle encoded edited and pre-edited transcripts. However, the downregulation of this protein appears not to affect the assembly of other putative subunits into MRB1.
Functional analysis of subunit MRB3010 of the mitochondrial binding complex 1 in Trypanosoma brucei.